(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Micronutrient deficiencies are a significant public health problem, causing substantial economic losses in many countries. Fortifying food with iron, iodine, and zinc is a widely recommended preventive measure, but policy implementation in some contexts remains challenging. This study aims to synthesize international evidence on the economic impact of the aforementioned three micronutrient fortification programs. Methods: A desk study was conducted using data from two databases, PubMed and Google Scholar, to screen relevant studies and synthesize key findings. Results: Evidence suggests that micronutrient fortification programs offer significant economic benefits. Iron fortification has a benefit-cost ratio ranging from 6:1 to 36:1 in different study contexts. The universal salt iodization program recorded a benefit-cost ratio of up to 30:1 and significantly reduced the burden of iodine deficiency disorders. Zinc fortification, particularly in countries with high wheat consumption, also showed positive effects with a benefit-cost ratio of approximately 14.6:1. Conclusion: The combined evidence suggests that micronutrient fortification in food is a preventative health intervention with significant economic benefits. The results may support the review, adjustment, and improvement of policies to strengthen micronutrient fortification in Vietnam.